The muscle sparing latissimus dorsi (MSLD) flap for secondary breast reconstruction based on reverse flow from intercostal vessels. Issue 1 (January 2020) - Sakharpe, Aniket K.; Cook, Jonathan; Newman, Martin I.; Barnavon, Yoav
Summary: The muscle-sparing latissimus dorsi (MSLD) flap is a modification by Saint Cyr of the traditional latissimus dorsi flap. While the flap is commonly based on the thoracodorsal artery pedicle, flap design based on reversed flow from the serratus branch has also been well documented. Uncertainty over the availability of adequate arterial inflow to support a pedicled MSLD flap is a potential concern in secondary breast reconstruction for previous surgery may have compromised the thoracodorsal pedicle and/or its branches. Herein, we describe how the MSLD flap can be utilized for breast reconstruction in such cases, even when the thoracodorsal artery and its serratus branch are found to have be ligated, by relying on reversed flow via the intercostal arteries. We present three female patients we were able to use the MSLD flap for reconstruction based on reversed flow via the descending branch of the thoracodorsal artery supplied by intercostal perforators. All patients had satisfactory aesthetic outcomes with a minimum of 6 month's follow-up.